Protection of Product Appearances Assisted or Generated by Artificial Intelligence - Repas, Martina (Od algoritma do prava: Pravni, ekonomski in kulturni izzivi umetne inteligence, 2025)
The impact of the increasing prevalence of artificial intelligence technology is reflected in many legal areas, including the field of designs, which represents one of the intellectual property rights that protect the appearance of a product. Artificial intelligence can be included in the design process as a tool, or it can be an independent designer. When used solely as a tool, the result is called an artificial intelligence-assisted design, while the one that artificial intelligence independently develops is called an artificial intelligence-generated design. This chapter highlights legal issues regarding the possibility of artificial intelligence acting as a designer or as a holder of a design. It further discusses the possibilities of protecting the appearance of a product created by or with the help of artificial intelligence, as well as the so-called input and output infringements of existing designs with product appearances created by or with the help of artificial intelligence.